Low investment farrowing facilities - James P Murphy (Kansas Agricultural Experiment Station Research Reports, 1988)
Low investment farrowing facilities can be divided into three categories, depending on the level of investment. At the lowest investment level, an individual farrowing shelter that has no floor is utilized. The shelter can be as simple as two sheets of plywood nailed together to create an A frame. Sometimes, rounded "quonset" shelters also are utilized. Since the weather protection is somewhat limited, these types of shelters are normally used to farrow only in the spring and fall. This is sometimes called the two-litter system. Farrowing is normally done on pastures. The shelters utilize no supplemental heat and have no permanent water supply. The shelters are moved each time they are used. Since farrowing is planned during mild weather, shelters are not insulated and are intended mainly to keep the sow and litter dry.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Farrowing; Quonset